Design of New Resonant Haloscopes in the Search for the Dark Matter Axion: A Review of the First Steps in the RADES Collaboration - Alejandro Díaz-Morcillo; José María García Barceló; Antonio José Lozano Guerrero; Pablo Navarro; Benito Gimeno; Sergio Arguedas Cuendis; Alejandro Álvarez Melcón; Cristian Cogollos; Sergio Calatroni; Babette Döbrich; Juan Daniel Gallego-Puyol; Jessica Golm; et al. (Universe, 2021)
With the increasing interest in dark matter axion detection through haloscopes, in which different international groups are currently involved, the RADES group was established in 2016 with the goal of developing very sensitive detection systems to be operated in dipole magnets. This review deals with the work developed by this collaboration during its first five years: from the first designs—based on the multi-cavity concept, aiming to increase the haloscope volume, and thereby improve sensitivity—to their evolution, data acquisition design, and finally, the first experimental run. Moreover, the envisaged work within RADES for both dipole and solenoid magnets in the short and medium term is also presented.